1991
DOI: 10.1063/1.857913
|View full text |Cite
|
Sign up to set email alerts
|

The secondary instability in Goertler flow

Abstract: The ‘‘high-frequency’’ secondary instability of nonlinearity developed and strongly modified Goertler vortices is numerically studied by considering two kinds of secondary instability modes, i.e., sinuous modes and varicose modes. A spectral collocation method with Chebyshev polynomials is used for calculations. It is found that secondary instabilities are more correlated with the vertical vorticity and the sinuous type disturbance would prevail over the varicose one for the same frequency and streamwise wave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
64
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 4 publications
10
64
0
Order By: Relevance
“…The high inflectional shear layer is provided by vu/vy in the upwash (nO0) region in the centre of the mushroom and, as we now know, predominantly supports the varicose mode of secondary instability (Sabry et al 1990;Yu & Liu 1991;Souza et al 2004); this is discussed and shown earlier by Stuart (1965) as a region supporting intense oscillations. The normal-to-wall mean vorticity, vu/vz, provides strong inflectional shear layers when viewed in the normal-to-wall direction in the likes of a jet or a wake profile and this partially supports the sinuous mode (Sabry et al 1990;Yu & Liu 1991). In terms of energy conversion from the mean flow to the fluctuations, there are now the dual mechanisms The fluctuation temperature is simply a passive scalar, with scales imposed by the advection velocities.…”
Section: Discussion Of Physical Mechanisms Of Developing Nonlinear Sementioning
confidence: 89%
See 4 more Smart Citations
“…The high inflectional shear layer is provided by vu/vy in the upwash (nO0) region in the centre of the mushroom and, as we now know, predominantly supports the varicose mode of secondary instability (Sabry et al 1990;Yu & Liu 1991;Souza et al 2004); this is discussed and shown earlier by Stuart (1965) as a region supporting intense oscillations. The normal-to-wall mean vorticity, vu/vz, provides strong inflectional shear layers when viewed in the normal-to-wall direction in the likes of a jet or a wake profile and this partially supports the sinuous mode (Sabry et al 1990;Yu & Liu 1991). In terms of energy conversion from the mean flow to the fluctuations, there are now the dual mechanisms The fluctuation temperature is simply a passive scalar, with scales imposed by the advection velocities.…”
Section: Discussion Of Physical Mechanisms Of Developing Nonlinear Sementioning
confidence: 89%
“…The first is the familiar normal-to-wall advection of the spanwise vorticity in parallel or nearly parallel shear flows (Stuart 1956a(Stuart ,b, 1958, which tends to reinforce travelling waves of an opportune phase relation as explained by Lin (1955); the second is the spanwise advection of normal-to-wall vorticity similar to the instability of a three-dimensional steady vortex flow (Sabry et al 1990;Yu & Liu 1991, 1994. The three-dimensional nature of the streamwise velocity can be visualized locally as a two-dimensional one in the cross-sectional yz -plane bounded by the mushroom-like structure (e.g.…”
Section: Discussion Of Physical Mechanisms Of Developing Nonlinear Sementioning
confidence: 99%
See 3 more Smart Citations